Pembelajaran Metode At-Tartil dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Untung Khoiruddin (Universitas Islam Tribakti Lirboyo Kediri, 2020)
This study aims to determine the learning of the at-Tartil method as well as the supporting and inhibiting factors in learning the at-Tartil method in improving the ability to read the Qur'an at TPQ Wildaanul Muslimin Gondang Manis Jombang. This research uses qualitative methods with descriptive qualitative research. With data collection techniques through observation, interviews and documentation. Then analyzed and checked the validity of the data through extended research, diligent research and triangulation, namely source triangulation, technique and time triangulation. The results showed that (1) the learning of the at-Tartil method in improving the ability to read the Qur'an at TPQ Wildaanul Muslimin includes policies on the time of taking volume and al-Qur'an classes, classical learning models, individual learning models, rhythm in learning process, daily evaluation, and level evaluation. (2) Supporting factors in learning the at-Tartil method in improving the ability to read the Qur'an include the students' interest in learning the Qur'an, professional teachers, motivation for students, additional activities, good facilities and infrastructure and communication between teachers and guardians of students.